Evaluasi Peran Humas Bawaslu Melalui Kolaborasi Mahasiswa dan Aktivis pada Pemilu Serentak 2024 di Kota Binjai - Hengki Mangiring Parulian Simarmata; Doris Yolanda Saragih; Erwin Sirait; Poltak Pardamean Simarmara; Demak Claudia Yosephine Simanjuntak; Jusra Tampubolon (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
This Community Service (PKM) activity aims to evaluate the role of Bawaslu's public relations in increasing public participation in the 2024 Simultaneous Elections, through collaboration with students and activists. The activity was carried out in the form of a seminar and forum group discussion (FGD) involving 50 participants from students and activists in Binjai City. This event was held on March 6, 2025, at the Graha Kardopa Hotel. Through the presentation of material by speakers from Bawaslu North Sumatra, and Management Lecturers from Prima Indonesia University as well as open discussion sessions, this activity encourages a deeper understanding of the strategic role of public communication and public relations in the implementation of transparent and participatory elections. The evaluation results showed that collaboration between students, activists, and Bawaslu was able to strengthen the effectiveness of political communication and increase the participatory awareness of the younger generation. This activity is expected to be a model of educational synergy between election organizing institutions and civil society groups in supporting healthy and inclusive democratic practices.